1987
DOI: 10.1007/bf00142713
|View full text |Cite
|
Sign up to set email alerts
|

A morphological description of human cataractous lenses by SEM

Abstract: Human cataractous lenses from patients of advanced age (101 & 85 year) were investigated by SEM. Various aspects of the cataract morphology could be observed. Even when the overall shape of the lens fibres had remained unchanged (although the typical ball and socket interconnections were barely visible) the homogeneous fibre content had changed into fibrillar and/or granular material, or the lens fibres had been (partly) hollowed out. Where there was shrinkage of the originally hexagonally-shaped lens fibres t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In both cases part of the lens-fibre contents is lost; a phenomenon which has been described before [6]. In the early stages of cataract formation only some of the lens-fibres are affected in this way and vision is often not directly affected because the abnormal fibres are located outside the pupillary area [1,4].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In both cases part of the lens-fibre contents is lost; a phenomenon which has been described before [6]. In the early stages of cataract formation only some of the lens-fibres are affected in this way and vision is often not directly affected because the abnormal fibres are located outside the pupillary area [1,4].…”
Section: Discussionmentioning
confidence: 98%
“…and OsO 4 solutions, dehydrated in ethanol and critical-point dried in liq. CO 2 as described before [6]. After drying, the lenses were carefully fractured approximately equatorially and, after gluing onto specimen-holders, sputtered with Au, appr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and OsO4 solutions, dehydrated in ethanol, dried by the critical point method with liq. CO2 as described before [2]. After gluing onto a specimen-holder the ring was sputtered with Au, appr.…”
Section: Methodsmentioning
confidence: 99%
“…With the help of a special glass cannula with a very blunt tip, developed by Pek van Andel, small quantities of secondary cataract material can be removed locally, without interfering with the functioning oftheintra-ocular lens. Jongebloed et al [1] have already indicated that remnants of lens-fibre material may lead to the development of a Soemmering's ring, for example, a typical aspect of secondary cataract. The aim of this study was to compare, by means of SEM, secondary cataract material from three parients; material which had been collected with the glass cannula and had resided for different periods of time in the eyes of these patients.…”
Section: Introductionmentioning
confidence: 99%